Sistema especialista para a monitoração do processo de degradação de medidores tipo indução de energia elétrica ativa - Silva, Marcelo R. [UNESP]; Luigi, G. [UNESP]; Ediléu, H. C.; Sciamana, Márcio; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper presents a methodology and software for hazard rate analysis of induction type watt-hour meters, considering the main variables related with the degradation process of these meters, for the Elektro Electricity and Services SA. The modeling developed to calculate the watt-hour meters hazard rate was implemented in a tool through a user friendly platform, in Delphi language, enabling not only hazard rate analysis, but also a classification by risk range, localization of installation for the analyzed meters, and, allowing, through an expert system, the sampling of induction type watt-hour meters, based on the model risk developed with artificial intelligence, with the mainly goal of follow and manage the process of degradation, maintenance and replacement of these meters. © 2010 IEEE.
Keywords: Artificial Intelligence; Expert system for sampling; Hazard rate; Induction type Watt-hour meters; Model risk; Degradation process; Delphi language; Hazard rates; User-friendly platforms; Artificial intelligence; Degradation; Expert systems; Hazards; Instruments; Watt hour meters